The Relationship between the Use of Who Surgical Safety Checklist and Implementation of Surgery Patient Safety - Mohamad Syah Insyah; Eko Suryani; Sapta Rahayu Noamperani (GLOBAL HEALTH SCIENCE GROUP, 2023)
Patient safety is very important in the operating room to prevent death and complications due to surgery and is a variable for measuring and evaluating the quality of nursing services that have an impact on health services. The mortality rate due to Unexpected Events (KTD) in hospitalized patients is 33.6 million per year. The patient safety program aims to reduce the number of unexpected events (KTD) that often occur in patients while hospitalized so that it is very detrimental to both the patient himself and the hospital. Efforts to improve the quality of surgical services include using the WHO Surgical Safety Checklist. Knowing the relationship between the use of the WHO Surgical Safety Checklist and the implementation of patient safety operations at Depati Hamzah Hospital, Pangkalpinang City. This research is a quantitative observational method with a cross-sectional design. The population of this study were anesthesiologists and surgical nurses at Depati Hamzah Hospital, Pangkalpinang City for one month, March 1 - March 30, 2023 with a sample of 30 people. Statistical test using the Chi-Square test. The results showed that all Anesthesiologists and Surgical Nurses filled out a complete Surgical Safety Checklist sheet (83.3%), and improving the implementation of patient safety showed the level of patient safety (83.3%). The results of the study showed that there was a relationship between the use of a surgical safety checklist and the implementation of surgical patient safety with a value of p = 0.004. There is a relationship between the use of a surgical safety checklist who and the implementation of surgical patient safety.